ANALISIS KINERJA PERUSAHAAN DENGAN PENDEKATAN BALANCED SCORECARD (Studi pada PT. Surveyor Indonesia Cabang Medan) - Anggraini Kahar; Zulbahridar Zulbahridar; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze the performance of PT. Surveyor Indonesia Branch Medan with balanced scorecard approach. Population in research service user companies, customers, and employees at PT. Surveyor Indonesia Branch Medan. In this study the sample was taken from 10 service user companies, 30 customers, and 40 employees in PT. Surveyor Indonesia Branch Medan. Methods of data collection with questionnaires, documentation, and literature study. Data analysis uses measurement of four balanced scorecard perspective that is financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The results of this study found that: 1) financial perspective as measured by ROI and profit margin decreased, while operating ratio increased in 2015; 2) customer perspective shows that the customer is satisfied and there is an increase in customer retention; 3) internal process perspective shows that in PT. Surveyor Indonesia Branch Medan in 2015 to innovate with product development; And 4) learning and growth perspective shows that employees are satisfied, while employee retention increases in Year 2015. Overall, the performance of PT. Indonesia Surveyor Branch Medan from 4 balanced scorecard perspective is good enoughKeywords: performance, balanced scorecard